Árbitro de emergencia: el refuerzo de la tutela cautelar (ante causam) en el arbitraje institucional - Blanco García, Ana Isabel (2020)
This article seeks to highlight the work that arbitral institutions are undertaking to guarantee comprehensive arbitration protection, highlighting the adoption of interim measures, including the so-called ante causam interim measures. These measures, as their name suggests, are requested even before the claim is filed, when there is no arbitral tribunal, since it has not yet been formally constituted. The figure of the emergency arbitrator arises to deal with this need, avoiding that the decision on this type of measures is left in the hands of the jurisdictional bodies, mainly because of the difficulties that could arise from the determination of jurisdiction in international arbitrations.